Motivasi Generasi Muda Dalam Beruusahatani Padi Untuk Mewujudkan Ketahanan Pangan Di Kabupaten Lampung Selatan - Amalia, Suci; Nikmatullah, Dewangga; Yanfika, Helvi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Food commodities play a very important role in food security and the sustainability of people's lives in Indonesia, especially in South Lampung Regency. South Lampung Regency has the potential for food development, especially rice. One way to improve food security is to regenerate the main actors who are currently entering old age with the younger generation. Who has very high energy and likes a challenge. This study aims to (1) analyze the level of motivation of the young generation and the level of food security in South Lampung Regency, (2) analyze the factors that influence the level of motivation of the younger generation in rice farming on the level of food security either directly or indirectly. This research method uses descriptive analysis and path analysis. The results showed that: (1) the level of the young generation in South Lampung Regency is in the high category and the level of food security of the young generation in South Lampung Regency is in the medium category, (2) The role of agricultural extension workers and the availability of production facilities have a direct and indirect effect on the level of household food security, while the cosmopolitan level, land area, and the level of motivation of the younger generation in rice farming have a direct effect on the level of household food security.